Hak menentukan nasib sendiri dalam kerangka persatuan dan kesatuan bangsa Indonesia - Sulaiman, SH, (Fakulti Undang - Undang, 2000)

(untitled)
The article traces the development of the concept of self-determination under International law. Numerous case studies were discussed to reflect the growing need for a more uniform standard of the concept, which could be applicable on member states. It is conceded that the right to self-determination is recognized in domestic problems such as in Timor Timur in the Indonesian archipelago. This article seeks to highlight the legal implications of using the right of self-determination by separatist movements in wanting to have their own autonomy in several provinces of Indonesia